FEATURES ARTERIAL ANATOMY OF THE LIVER AND ENDOVASCULAR CHEMOEMBOLIZATION OF THE HEPATIC ARTERY IN THE TREATMENT OF PRIMARY AND METASTATIC LIVER CANCERS - V. V. Plechev; Sh. Kh. Gantsev; F. F. Mufazalov; V. Sh. Ishmetov; M. O. Loginov; R. A. Abdrakhmanov (Креативная хирургия и онкология, 2017)
This article presents an overview and results  of treatment of malignant neoplasms of the  liver hepatic artery  chemoembolization methods in 141 patients. The analysis  of  the results of this method of treatment.